Freedom, True and Morality in Politics and in International Relations - Kurnicki, Andrzej (Studia Gdańskie, 2023)
The United States is a federal republic whose citizens enjoy a dynamic political system, a strong tradition of the rule of law, robust freedom of speech and religious belief, and a wide range of other civil liberties. The First Amendment to the U.S. Constitution prevents the government from enacting laws that: govern the establishment of religion; prohibit the free exercise of religion; restriction of freedom of speech, freedom of the press and freedom of assembly. There is a growing tendency in global politics, academia and in diplomacy to accept hegemon state status and tendency to dominate all-important aspect of global power. The freedom and moral standards are rather viewing as a political ballast because man by nature and the states in particularly has a boundless wish for unrestricted power and to promote self-national interest regardless of international law, custom, culture or tradition. The XXI century crisis of freedom is at the root of the crisis of truth. In the conceptually contemporary world, John Paul II's voice clearly showed the inseparable link between freedom and truth. Pope philosophy of freedom is contrary to the concept of freedom from values, so widespread in contemporary culture, especially in the USA. Key words; freedom, morality, true, John Paul II, realism, natural law.